2010
DOI: 10.1186/2040-2392-1-13
|View full text |Cite
|
Sign up to set email alerts
|

Elevated cortisol during play is associated with age and social engagement in children with autism

Abstract: BackgroundThe hallmark characteristic of autism is impaired reciprocal social interaction. While children find social interaction stress-reducing, many children with autism may find social interaction stress-inducing. The current study was designed to examine stress responsivity as measured by cortisol by comparing children with autism to neurotypical peers during an ecologically valid 20-minute playground paradigm.MethodsThe experiment involved sets of three children: a child with autism, a neurotypical child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
166
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(181 citation statements)
references
References 64 publications
14
166
1
Order By: Relevance
“…Research investigating stress in children with and without ASD during an ecologically valid benign social interaction found that those with ASD had significantly higher cortisol levels, reflecting enhanced arousal from social engagement (Corbett et al, 2010). This study demonstrated that not just stressful social interaction but 'benign' social interaction results in the increase of cortisol in those with ASD.…”
Section: Protective Strategies Adverse Effects Of Cortisolmentioning
confidence: 55%
See 1 more Smart Citation
“…Research investigating stress in children with and without ASD during an ecologically valid benign social interaction found that those with ASD had significantly higher cortisol levels, reflecting enhanced arousal from social engagement (Corbett et al, 2010). This study demonstrated that not just stressful social interaction but 'benign' social interaction results in the increase of cortisol in those with ASD.…”
Section: Protective Strategies Adverse Effects Of Cortisolmentioning
confidence: 55%
“…Lorna Wing (1981) suggests that those with ASD lack the ability to understand the rules of social behaviour. Research investigating stress in children with and without ASD during an ecologically valid benign social interaction found that those with ASD had significantly higher cortisol levels, reflecting enhanced arousal from social engagement (Corbett, Schupp, Simon, Ryan, & Mendoza, 2010). Structural abnormalities found in the autistic amygdalae have been identified, which is significant as the amygdalae play an important role in social and emotional engagement (Toal et al, 2010).…”
Section: Social Cognitionmentioning
confidence: 99%
“…There is no association between depression characteristics and salivary cortisol levels [125]. Markedly enhanced blood or salivary cortisol response were found in ASD children when exposed to social stress [126,127]. In schizophrenia patients, salivary cortisol secretion was slightly increased by exposure to stress [128].…”
Section: Mood Disorders Asd and Schizophreniamentioning
confidence: 82%
“…Evening cortisol levels positively correlated to daily stressors in children with autism (Corbett et al, 2009). Moreover, increase in age of autistic children correlated with increased cortisol levels during social interaction stress (Corbett et al, 2010). CRH has also been shown to increase intestinal permeability of human colonic biopsies, while maternal separation stress and CRH are associated with a dysfunctional mucosal barrier in rodents (Soderholm et al, 2002).…”
Section: Perinatal Stressmentioning
confidence: 99%